2018
DOI: 10.1007/s12275-018-8228-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Schizonepeta tenuifolia Briquet against noroviruses via induction of antiviral interferons

Abstract: Human noroviruses are the causative agents of non-bacterial gastroenteritis worldwide. The rapid onset and resolution of disease symptoms suggest that innate immune responses are critical for controlling norovirus infection; however, no effective antivirals are yet available. The present study was conducted to examine the antiviral activities of Schizonepeta tenuifolia Briquet extract (STE) against noroviruses. Treatment of human norovirus replicon-bearing HG23 cells with STE at 5 and 10 mg/ml concentrations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…MNV infection in RAW cells induces a strong innate immune response, including interferon induction (66). Type I interferons in turn are able to affect host cell metabolism (67, 68) and exhibit a strong anti-MNV response (6971). Therefore, we determined whether 2DG inhibition of viral replication was dependent on type I interferon responses.…”
Section: Resultsmentioning
confidence: 99%
“…MNV infection in RAW cells induces a strong innate immune response, including interferon induction (66). Type I interferons in turn are able to affect host cell metabolism (67, 68) and exhibit a strong anti-MNV response (6971). Therefore, we determined whether 2DG inhibition of viral replication was dependent on type I interferon responses.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Chemical studies revealed that SS contained volatile oils, flavonoids, organic acids, etc. [7][8][9] Research into pharmacological activities of the oils accumulated by SS possesses anti-inflammatory, [10] antioxidant, [11] analgesia, [12] antineoplastic [13,14] and antiviral [15,16] properties. Thus, the volatile components could be selected as marker compounds for quality evaluation of SS.…”
Section: Introductionmentioning
confidence: 99%
“…MNV infection in RAW cells induces a strong innate immune response, including interferon induction (66). Type I Interferons in turn are able to affect host cell metabolism (67, 68), and exhibit a strong anti-MNV response (6971). Therefore, we determined whether 2DG inhibition of viral replication was dependent on type I interferon responses.…”
Section: Resultsmentioning
confidence: 99%